2013
DOI: 10.1073/pnas.1218126110
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosylation of HDAC2 regulates the expression of the chromatin-remodeling factor Brm during radial neuron migration

Abstract: Dynamic epigenetic modifications play a key role in mediating the expression of genes required for neuronal development. We previously identified nitric oxide (NO) as a signaling molecule that mediates S-nitrosylation of histone deacetylase 2 (HDAC2) and epigenetic changes in neurons. Here, we show that HDAC2 nitrosylation regulates neuronal radial migration during cortical development. Bead-array analysis performed in the developing cortex revealed that brahma (Brm), a subunit of the ATP-dependent chromatin-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 41 publications
0
51
1
1
Order By: Relevance
“…Recent work from our lab (Nott et al., 2008, Nott et al., 2013) and others (Hagelkruys et al., 2014, Hagelkruys et al., 2015) demonstrated that the class I histone deacetylases HDAC1 and HDAC2 control the expression of genes necessary for neuronal development. Class I HDACs do not bind DNA directly and are found within large multiprotein complexes that confer target specificity (Haberland et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work from our lab (Nott et al., 2008, Nott et al., 2013) and others (Hagelkruys et al., 2014, Hagelkruys et al., 2015) demonstrated that the class I histone deacetylases HDAC1 and HDAC2 control the expression of genes necessary for neuronal development. Class I HDACs do not bind DNA directly and are found within large multiprotein complexes that confer target specificity (Haberland et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The chromatin function of HDAC2 can be negatively regulated following a posttranslational modification by nitric oxide, called S -nitrosylation [24]. HDAC2 nitrosylation has been shown to have a role in regulating both cortical development and memory formation [22, 24, 25]. Interestingly, neuronal nitric oxide synthase (nNOS), an enzyme which provides a major source of nitric oxide in neurons, is highly expressed specifically in interneuron cell populations in the adult mouse cortex [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…ADH5 neuronal differentiation antagonism seems to depend on ADH5 catalytic activity. It was reported that S-nitrosation of HDAC2 mediates neurotrophin-dependent chromatin remodeling and the activation of neuronal development genes (7,30), and likewise HDAC inhibition is able to promote neuronal differentiation (31). Our study reveals that ADH5 serves as a denitrosation enzyme for HDAC2, and programmed down-regulation of AHD5 may lead to a derepression of HDAC2 by increasing its S-nitrosation, which consequently facilitates specific gene expression resulting in neuronal differentiation and development.…”
Section: Resultsmentioning
confidence: 60%
“…in denitrosating both S-nitrosoglutathione and specific S-nitrosated proteins (11,28,29). Considering that S-nitrosation of HDAC2 is required for epigenetic activation of neuronal differentiation-associated genes (7,30), we hypothesize that ADH5 may antagonize neurogenesis by denitrosating HDAC2. To test this, we first investigated whether S-nitrosated HDAC2 is a target of ADH5.…”
Section: Resultsmentioning
confidence: 95%